(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
An essential component of guaranteeing the security of underground coal mines is the stability of underground areas. Coal pillars are left in place in underground coal mines to stabilize opened regions where excavations have redistributed in situ stresses. The designs of pillars have been developed in accordance with the necessary safety and economic constraints. The safe and cost-effective design of mining pillars, particularly coal pillars, is influenced by various factors. The purpose of this publication, which is a portion of a doctoral thesis, is to support a theory regarding the impact of methane emissions on the stability of coal pillars. This topic has not received much attention in the literature. The pillar design’s initially effective parameters are examined and categorized in this study. The impact of coal gas emissions on the stability of coal roofs, pillars, and walls are investigated for the first time. Previous research on the mechanical behavior of coal exposed to different kinds of gases is examined for this aim. The literature’s findings also showed that coal’s mechanical properties will decrease when exposed to gases, including shear strength, elastic modulus, and uniaxial compressive strength. The coal texture develops joints and cracks as a result of gas adsorption and emission, which lowers the mechanical properties of the coal and causes instabilities in underground spaces. The literature suggests that gas emissions from coal pillars and walls in underground mines most likely produced unpredictable instability and outburst. To the best of the authors’ knowledge and ability to determine, there is an absence of critical literature reviews on the mechanical properties of coal during gas emissions, which is the topic of this work.